Lumbar microdiscectomy and lumbar decompression improve functional outcomes and depression scores - Tharin, Suzanne; Mayer, Eric; Krishnaney, Ajit (Evidence-Based Spine-Care Journal, 2012)
Consistent with EBSJ’s commitment to fostering quality research, we are pleased to feature some of the most highly rated abstracts from the 10th Annual AOSpine North America Fellows Forum in Banff, Canada. Enhancing the quality of evidence in spine care means acknowledging and supporting the efforts of young researchers within our AOSpine North America network. We look forward to seeing more from these promising researchers in the future.